2020
DOI: 10.3390/jintelligence8040036
|View full text |Cite
|
Sign up to set email alerts
|

Effect Sizes, Power, and Biases in Intelligence Research: A Meta-Meta-Analysis

Abstract: In this meta-study, we analyzed 2442 effect sizes from 131 meta-analyses in intelligence research, published from 1984 to 2014, to estimate the average effect size, median power, and evidence for bias. We found that the average effect size in intelligence research was a Pearson’s correlation of 0.26, and the median sample size was 60. Furthermore, across primary studies, we found a median power of 11.9% to detect a small effect, 54.5% to detect a medium effect, and 93.9% to detect a large effect. We documented… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 120 publications
1
15
0
Order By: Relevance
“…Next, we discuss the feasibility of using a latent variable model instead of traditional ANOVA methods, when the sample sizes per group are small (N = 50 to N = 100), and the expected effect size is small to moderate (Cohen's d = 0.40). These estimates coincide with the median sample size (N = 60) and median weighted effect size (r = 0.26) found in approximately 2400 effect sizes in 131 meta-analyses in intelligence research (Nuijten, van Assen, Augusteijn, Crompvoets, & Wicherts, 2019).…”
Section: Minimal Requirements Under Measurement Invariancesupporting
confidence: 81%
“…Next, we discuss the feasibility of using a latent variable model instead of traditional ANOVA methods, when the sample sizes per group are small (N = 50 to N = 100), and the expected effect size is small to moderate (Cohen's d = 0.40). These estimates coincide with the median sample size (N = 60) and median weighted effect size (r = 0.26) found in approximately 2400 effect sizes in 131 meta-analyses in intelligence research (Nuijten, van Assen, Augusteijn, Crompvoets, & Wicherts, 2019).…”
Section: Minimal Requirements Under Measurement Invariancesupporting
confidence: 81%
“…For instance, an examination of 2261 psychology papers by Szucs and Ioannidis (2017) found that the mean power for detecting small effects in psychology was 23%, 60% for medium effects, and 78% for large effects, while Stanley et al's (2018) review of 200 meta-analyses calculated a median overall statistical power of only 36%. Most recently, Nuijten et al (2020) found that, in intelligence research, studies only had 11.9% power to detect small effects, along with a median sample size of just 60 participants. It appears that several decades after Cohen's first review, very few studies still come close to the widely accepted minimum power level of 80%.…”
Section: Introductionmentioning
confidence: 99%
“…The second sample derived from a review of the literature about intelligence and IQ (Nuijten, Van Assen, Augusteijn, Crompvoets, & Wicherts, 2018),in which the authors analyzed meta‐analyses found in ISI Web of Science as of August 2014 to estimate the typical effect size, the median power, and patterns of biases. They included quantitative meta‐analyses with complete data tables with sufficient information to calculate or retrieve primary study effect size and standard error.…”
Section: Methodsmentioning
confidence: 99%